Ethnic Cleavages: The Descendant and Clan Sentiment on Local Executive Election in North Tapanuli, North Sumatera Province - Damanik, Erond Litno (Komunitas, 2019)
The foundation of this study is political anthropology to see the phenomenon of ethnicity in local politics in the era of democratic decentralization. The study focused on ethnic cleavages in the form of strengthening social units that appear through descendant and clan sentiments at the moment of the Pemilukada (Local Executive Election). Therefore, the purpose of this study is to understand the phenomenon of ethnic cleavages which highlights descendant and clan sentiments in four districts in north of Tapanuli in the Pemilukada. Local politics at the time of democratic decentralization was not only used to expand the four cultural areas, namely Silindung, Humbang, Toba and Samosir, but also strengthen descent and clan sentiments in the Pemilukada. Although, the population in these four regions is a Toba ethnic group, its members destabilize and negate each other. This phenomenon originated from the domination of Silindung from the colonial era to the Reformation. Through Pemilukada, the descent and clan sentiments are used to blockade other candidates as well as mobilize selecting candidates from similar groups and clans. The promise of Pemilukada is channeled through a monopoly to fill government positions from one lineage group and clan. The approach of this problem is used Dunning and Harrison's theory about Cross-Cutting Cleavages and Ethnic Voting. The data collection was carried out through in-depth interviews with subjects, namely descendants and clans in four districts in north of Tapanuli. The results of the study show that: (i) ethnic cleavages occur because of the utilization and mobilization of social units namely descent and clan groups in the moment of Pemilukada, (ii) the strengthening of descent and clan group sentiments in Pemilukada is the impact of competition and contestation which are packaged as political capital for gained power, and (ii) political actors redefined ethnicity as 'Orang Toba' to smaller identities namely descendants and clans in each cultural region. The Toba ethnic groups are more loyal to their descendants and clan identities than their identities as 'Orang Toba'. Although the political analysis of the flow was considered less relevant as a result of the strengthening of the issue of interest in the Pemilukada, but the strengthening of division in ethnicity became a strong indication of ethnic cleavages and the game of primordialism during the Pemilukada.